New Dimension to Green Buildings: Turning Green into Occupant Well-Being - Yang Fu (MDPI AG, 2021)
A series of international conferences and initiatives, such as the Habitat III New Urban Agenda and UN Sustainable Development Goals, have urged industry, scholars, and policymakers to create an inclusive and sustainable built environment for all in the coming era of cities. Green building schemes, which have been gaining momentum over recent decades, are one of the most influential measures that have been taken to promote urban sustainability. However, due to disciplinary characteristics, most current studies share a techno-engineering focus. Seldom do they answer the question: will green buildings make a difference to the occupants? This paper explains how, and to what extent, green features and design contribute to different dimensions of occupant well-being by conducting a systematic and comprehensive review of current journal articles and industrial reports. It provides an alternative, occupant-oriented perspective to the conventional discourse. A conceptual framework is developed, revealing that green building aspects are linked to six dimensions (three subjective and three objective) of occupant well-being. It further shows how different green features are linked with these dimensions through a detailed examination of the literature. Finally, suggestions are provided based on the research findings for the direction of future green building development and empirical research.